2017
DOI: 10.3390/sinusitis2030005
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Frequency Treatment for Facial Pain Caused by Chronic Rhinosinusitis: A Pilot Study

Abstract: Chronic rhinosinusitis (CRS) is a common disease that affects over 200 million patients worldwide. CRS often presents with facial pain, which is considered an important criterion for the diagnosis of CRS. A single-arm clinical study was designed to test the effect of simultaneous high (1 MHz) and low frequencies (70-80 Hz) on facial pain in 14 CRS patients at the Sarah Bush Lincoln Health Center, Mattoon, IL, USA. We used two quality of life (QOL) instruments to test the effect of multimodal frequencies on pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…Again, the mechanisms of action are not clear but may be related to vibration-induced modulation of pain receptors or inhibition of the parasympathetic system. 10 As with many pilot studies, there are limitations of this study. First, given that patients were not randomized or blinded, a placebo effect is possible.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Again, the mechanisms of action are not clear but may be related to vibration-induced modulation of pain receptors or inhibition of the parasympathetic system. 10 As with many pilot studies, there are limitations of this study. First, given that patients were not randomized or blinded, a placebo effect is possible.…”
Section: Discussionmentioning
confidence: 91%
“…Although we initially chose to measure pain and headache scores to ensure that patients were not experiencing adverse effects of ART, we found that patients not only did not worsen, but also that patients who had some baseline pain and headache (VAS ≥ 1) experienced a notable improvement. Again, the mechanisms of action are not clear but may be related to vibration‐induced modulation of pain receptors or inhibition of the parasympathetic system 10 …”
Section: Discussionmentioning
confidence: 99%
“…Mean 22‐item Sino‐Nasal Outcome Test (SNOT‐22) improvement over 2 weeks was 14.11 ( p < 0.05), exceeding the minimal clinically important difference (MCID). The authors of this study were associated with the company that developed the AxioSonic device 13 …”
Section: Resultsmentioning
confidence: 99%